Profile of Sentinel 2 Vegetation Index as Impact of Forest Change: Case Study Enrekang Regency 2019 – 2024 Periods - Syamsu Rijal; Munajat Nursaputra; Afandi Ahmad; Chairil; Revalina Theresia Sinaga; Helen Natalia Kasang; Yulanda Angel Tangdilintin; Anugrahandini Natsir; Nurul Muchlisah Basri (Fakultas Kehutanan, Universitas Hasanuddin, 2025)
Land cover change is one of the key factors influencing environmental quality and ecosystem dynamics, especially in areas experiencing pressure from land use and the growth of anthropogenic activities. The Indonesian Government’s commitment to reducing greenhouse gas emissions from the land-use sector by national FOLU Net Sink 2030. This study was conducted to provide a quantitative of the vegetation indices as a response to forest cover dynamic. The study showed that the SAVI and NDVI are able to describe the change of forest to other vegetated land cover. Meanwhile, EVI index only sensitive to the change of forest to settlement area. It could be concluded that monitoring of forest change could be done by utilizing vegetation indices from Sentinel 2 satellite imagery. However, it is also necessary to pay attention to variables such as weather data, pioneer vegetation on the shrub or bareland area, as well as band processing of satellite imagery that could affect the sensitivity of vegetation indices to land cover changes in an area.